TANGGUNGJAWAB BADAN PERTANAHAN NASIONAL (BPN) DALAM KEGIATAN PENGUKURAN DAN PEMETAAN BIDANG TANAH DALAM RANGKA PENERBITAN SERTIPIKAT MENURUT PP NO. 24 TAHUN 1997 DAN PMA/KBPN NO. 3 TAHUN 1997 (CONTOH KASUS PUTUSAN PENGADILAN NEGERI JAKARTA BARAT NOMOR 720/Pdt.G/2019/PN.Jkt.Brt.) - Susanto Agata Margita (Fakultas Hukum Universitas Tarumanagara, 2021)
This article is entitled “Responsibility of the National Land Agency (BPN) in the Activities of Measurement and Mapping of Land Fields in the Context of Issuing Certificates according to Government Regulation No. 24/1997 and PMA/KBPN No. 3 of 1997 (Example Case of West Jakarta District Court Decision Number 720/Pdt.G/2019/PN.Jkt.Brt.)